O homem livre em Deus por Bento Espinosa - Leite, Wiltonn William (My University, 2016)
This thesis aims to investigate how a certain and defined man can be free in a universe determined to exist exclusively by the necessity of Deus sive Natura, as Benedict Spinoza affirm. Therefore, it does the review of this author emphasizing his books Ethica and Tractatus de Intellectus Emendatione and some of his commentators. It starts with the Spinoza’s idea of the existence of a unique absolutely infinite substance – Deus sive Natura – self-cause of itself and the entire universe (spinozist model of causality). It makes explicit as the man having reformed his intellect or his intelligence he can know himself and the others things by their adequate causes which leads him to learn and understand himself and the things in his (their) perfect reality. It is discussed this man, adequate cause of himself, and the consequences for his existence with himself (conatus) in the encounter (occursus) with the other (the other man).An ethical perspective, known things by their adequate causes by an absolute affective rationalism (emotional reason), the man acts actively, composing with the other man a relationship of friendship. Trying to persevere himself in his being, he respects and preserves the other, resulting in the increase of his (their) power(s) to act and his (their) energy(s) to exist. This understanding can result in the establishment of the closest state of human nature: the democratic state. So, finally, it is concluded that the free and autonomous man in God is the spiritual automaton. He is free when – having the proper knowledge of things – he is, operates, moves, lives and exists in act according to what God commands him. He knows God and this is the beatitude.
Essa dissertação tem como objetivo investigar como um determinado e definido homem pode ser livre em um universo determinado a existir exclusivamente pela necessidade da natureza de Deus sive Natura como afirma Bento Espinosa. Para tanto, faz-se a revisão da obra desse autor com ênfase em seus livros Ethica e Tratatus de Intellectus Emendatione e de alguns de seus comentadores. Parte-se da ideia espinosista da existência de uma única substância absolutamente infinita – Deus sive Natura – que ao causar-se causa o universo inteiro (modelo espinosiano de causalidade). Explicita-se como o homem tendo reformado seu intelecto ou sua inteligência pode vir a conhecer a si e as coisas por suas causas adequadas o que lhe leva a apreender e compreender a si mesmo e as coisas em sua perfeita realidade. Discute-se este homem – causa adquada de si mesmo – e sua consequência para sua existência em ato, consigo mesmo (conatus) no encontro (occursus) com o outro (o outro homem). Numa perspectiva ética, conhecidas as coisas por suas causas adequadas, por absoluto racionalismo afetivo (razão afetiva), o homem agindo ativamente, compõe-se com o outro em uma relação de amizade. Procurando se perseverar em si mesmo, respeita e preserva o outro, o que resulta no aumento de sua(s) potência(s) para agir e de sua energia(s) para existir. Essa compreensão pode resultar no estabelecimento do estado mais próximo da natureza humana: o estado democrático. Assim, finalmente, conclui-se que o homem livre e autônomo em Deus é o autômato espiritual. É livre quando, tendo o conhecimento adequado das coisas, ele é, está, opera, se move, vive e existe em ato segundo o que Deus lhe ordena. Ele conhece a Deus e isto é a beatitude.
Keywords: Liberdade; Ontologia; Razão; Filosofia; Liberty; Ontology; Reason; Philosophy; Spinoza, Benedictus de, 1632-1677